Peningkatan Kapasitas Digital UMKM melalui Sosialisasi Pemanfaatan Website di Kampung Batik Laweyan - Wiwit Supriyanti; Nor’ Ain Abdullah; Ipin Prasojo; Arif Nugraha Hernanjaya; Eko Nugroho; Shofiyatun (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Enhancing competitiveness in the digital economy era remains a significant challenge. However, many Micro, Small, and Medium Enterprises (MSMEs) still lack the knowledge and skills to effectively utilize technology, particularly websites as a marketing medium. This community service activity aims to improve the digital capacity of MSME actors in Kampung Batik Laweyan through socialization and training on website utilization. The implementation methods include needs identification, material preparation, socialization, hands-on training, and activity evaluation. The results of the program indicate an increase in participants’ understanding of digital marketing concepts as well as their basic ability to manage websites as tools for promotion and transactions. In addition, participants have begun to utilize website features such as product catalogs and content management independently. This activity contributes to promoting the digital transformation of MSMEs and expanding their online marketing reach.